Incidence of obesity in students at alauddin state islamic university makassar : A Cross Sectional Study - Alam, Syamsul; Syahrir, Sukfitryanti; Adha, A. Syamsiah; Achmad, Pratiwi Maharani (CORE JOURNAL, 2022)
Obesity is a condition in people who are overweight because fat accumulates in the body. Obesity is a multifactorial disease and the increase in obesity is often associated with the habit of consuming more food than needed and the number of calories burned. Based on WHO data, the prevalence of global obesity has almost tripled between 1975 and 2020. This is corroborated by data from the 2018 Basic Health Study (RISKESDAS), which experienced an increase in obesity data from 2013 to 2018. The purpose of this study was to determine the relationship between sedentary behavior and physical activity. , eating patterns and sleep duration of adolescents with the incidence of obesity. This type of research is a quantitative research with an analytic observational approach with a cross sectional study design method. Class of 2021 students at Alauddin Makassar State Islamic University, totaling 156 people, were used as research samples. The sampling technique in this study used accidental sampling. The results of this study indicated that based on the results of the bivariate test it was found that sedentary behavior had a p value of 0.000; physical activity 0.003; diet 0.000; sleep duration 0.000 indicates that there is a relationship between sedentary behavior, physical activity, eating patterns and sleep duration on the incidence of obesity. The conclusion of this study is sedentary behavior, physical activity, eating patterns and sleep duration are factors that influence the incidence of obesity in adolescents at Alauddin State Islamic University Makassar.